Clinical assessment of cemento‐osseous dysplasia based on three‐dimensional diagnostic imaging: A case report. (1st February 2021) - Shibata, Naoki; Inamoto, Kyoko; Naitoh, Munetaka; Ariji, Eiichiro
Abstract: Cemento‐osseous dysplasia (COD) is a lesion in which periapical bone is replaced by fibrous tissue, including osseous or cementum‐like tissue. In the initial stage of COD, radiolucencies are noted at the root apex on periapical radiography, which can be confused with apical periodontitis. Understanding of correct pathological condition and careful assessment of COD is critical to avoid unnecessary endodontic interventions in healthy teeth. This report describes the ability and usefulness of cone‐beam computed tomography (CBCT) and multi‐slice computed tomography (MSCT) to detect COD. The findings in this case suggest that MSCT is more appropriate than CBCT, especially for patients with early‐ to middle‐stage COD. However, the radiation dose is higher in MSCT than in CBCT; the application of MSCT should be limited to assessment of whether treatment or surgical management is necessary.